Concentração da solução nutritiva no cultivo do meloeiro em Sistema semi-hidropônico - Silva, Karen Mariany Pereira (2015)
The State of Rio Grande do Norte is the second largest exporter of melons from Brazil. It is in the region of Natal, which concentrates most of the production , the shortage of good quality water has limited the increase in irrigated area . The semi- hydroponic cultivation has become an alternative for allowing a production efficiency and ease the absorption of water and nutrients by plants. This study aimed to evaluate the growth, production and postharvest quality of melon Gaul ( Cucumis melo L. cv " NECTA " ) , grown in semi -hydroponic system. The survey was conducted in a greenhouse at the Department of Environmental Sciences and Technology of the Federal Rural University of semiarid - UFERSA , from June to August 2014. The experimental design was a randomized complete block design with five blocks and five replications , totaling 25 plants per experimental plots . We evaluated the effect of macronutrient five concentrations for the proportions of ( 12.5, 25, 50 , 75, 100%), the quantity of nutrients proposed for melon cultivation. Ten days after transplanting , the variables were analyzed : plant height ; stem diameter ; Leaf area ; number of leaves, fruit weight, transversal and longitudinal diameter , transverse and longitudinal internal cavity , thick peel and pulp , soluble solids, titratable acidity , pH, total sugars and fruit maturation relationship. Data were subjected to analysis of variance and comparison of means by Tukey test at 5 % probability. The variation of nutrient concentration influenced the behavior of the variables . The 50% concentration of nutrients provided greater weight and better fruit pulp thickness and smaller diameter stem. The concentration of 12.5 % of nutrient concentration, provided significant results for titratable acidity and soluble solids